Forecasting the Depression: Harvard versus Yale - Dominguez, Kathryn M.E.; Fair, Ray C.; Shapiro, Matthew D. (American Economic Review, 1988)
Was the Depression forecastable? After the crash, how long should it have taken contempo rary forecasters to realize how severe the downturn was going to be? These questions are addressed by studying the predictions of the Harv ard Economic Service and Yale's Irving Fisher during 1929 and the ear ly 1930s. The data assembled by the Harvard and Yale forecasters, tog ether with modern historical data, are subjected to statistical analy sis to learn whether their verbal pronouncements were consistent with the data. Both the Harvard and Yale forecasters were systematically too optimistic. Yet, nothing in the data suggests that the optimism w as unwarranted. Copyright 1988 by American Economic Association.